Exploration on the collaborative innovation path of college students' ideological education and psychological education - Lin, Cuixia; Lin, Keneng (Frontiers in Psychology, 2022)
As a highly practical educational activity, mental health education must be guided by rich theories in order to maintain the steady development of mental health education. Ideological education plays a predictive role in college students' crisis management, which can improve college students' psychological crisis management ability. This paper proposes an early warning index system and applies it to the construction of early warning mechanism, completes the qualitative and quantitative analysis of early warning information evaluation, and changes the situation that information evaluation only stays at the level of qualitative analysis in traditional methods. Quantitative analysis is more conducive to accurately predict the occurrence of psychological crisis. Through empirical research, this paper finds that there is a significant interaction between stressors and coping styles in the process of affecting mental health. The result of interaction is not only equal to the superposition of the influence of a single factor, but greater or less than the superposition of the influence of a single factor. The study found that there was a significant correlation between stressors and mental health. It is one of the many factors that affect mental health, and it is also the main reason to induce college students' psychological crisis. Mature coping styles are significantly positively correlated with mental health, while immature coping styles are significantly negatively correlated with mental health. This paper tests students, which is more conducive to the timely warning of psychological crisis.